Action Sequences, Habits, and Attention in Copying Strategies - Perez-Riveros, O (Cambridge University Press, 2022)
Understanding how culture evolves in society is an extremely difficult task. The bifocal stance theory (BST) deploys two copying strategies which can be linked to dual-system theories of behavior. BST would benefit from incorporating results from these theories, such as the evolution of attention to goals or steps of a behavioral sequence, and the role of the environment in prompting different copying strategies. Copyright © 2022 The Author(s).